Uncertainty and Cross-Border Banking Flows - Choi, Sangyup; Furceri, Davide (Washington, D.C. : International Monetary Fund, 2018)
While global uncertainty-measured by the VIX-has proven to be a robust global 'push' factor of international capital flows, there has been no systematic study assessing the role of country-specific uncertainty as a key (pull and push) factor of international capital flows. This paper tries to fill this gap in the literature by examining the effects of country-specific uncertainty shocks on cross-border banking flows using the confidential Bank for International Settlements Locational Banking Statistics data. The dyadic structure of this data allows to disentangle supply and demand factors and to better identify the effect of uncertainty shocks on cross-border banking flows. The results of this analysis suggest that: (i) uncertainty is both a push and pull factor that robustly predicts a decrease in both outflows (retrenchment) and inflows (stops); (ii) global banks rebalance their lending towards safer foreign borrowers from local borrowers when facing higher uncertainty; (iii) this rebalancing occurs only towards advanced economies (flight to quality), but not emerging market economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet